AUTOETNOGRAFICA WRITING AS CRITICISM TO THE REPRODUCTION OF THE POWER OF COLONIAL MATRIX IN THE TEACHING PERFORMANCE (Revista NUPEART, 2023)
By problematizing the reproduction of colonial power in acting as an art teacher at Cieja Ermelino Matarazzo, a project aimed at basic education for young people and adults offered by the city of São Paulo, I present the possibility of exercising an autoethnogra- phic writing, gestated in the experience as performer member of the Coletivo Parabelo. Through this autoethnographic gesture, I aim to highlight the sexist, racist and patriarchal bases conventio- nally naturalized inside and outside the school context, from the report of a performance class about the Brazilian artist Flávio de Carvalho's Experience No3 and its reverberations, as a way to trig- ger a process of self-criticism and self-transformation inherent to the praxis of researcher and professor performer.
Keywords: Performance class; Autoethnographic writing; Colonial power